2013
DOI: 10.1016/j.cub.2013.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Information Sharing in the Brain Indexes Consciousness in Noncommunicative Patients

Abstract: Neuronal theories of conscious access tentatively relate conscious perception to the integration and global broadcasting of information across distant cortical and thalamic areas. Experiments contrasting visible and invisible stimuli support this view and suggest that global neuronal communication may be detectable using scalp electroencephalography (EEG). However, whether global information sharing across brain areas also provides a specific signature of conscious state in awake but noncommunicating patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
342
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 313 publications
(382 citation statements)
references
References 42 publications
28
342
4
8
Order By: Relevance
“…Our results are also in agreement with several theories of consciousness (22,24) and earlier observations in sleep, anesthesia, and VS (18,(40)(41)(42)(43). Several theories of consciousness posit that distributed functional networks support conscious states and that loss of consciousness is indexed by alterations of these network patterns (22,24,42).…”
Section: Discussionsupporting
confidence: 81%
“…Our results are also in agreement with several theories of consciousness (22,24) and earlier observations in sleep, anesthesia, and VS (18,(40)(41)(42)(43). Several theories of consciousness posit that distributed functional networks support conscious states and that loss of consciousness is indexed by alterations of these network patterns (22,24,42).…”
Section: Discussionsupporting
confidence: 81%
“…Our finding is also consistent with previous literature that analysed EEG data with complementary methods based on clinical expertise (Forgacs et al, 2014) and information theory (King et al, 2013). This engenders confidence in the reliability of EEG as a valuable tool, as it suggests that different analytical methods could be used to deliver similarly capable diagnostic capabilities.…”
Section: Discussionsupporting
confidence: 81%
“…This engenders confidence in the reliability of EEG as a valuable tool, as it suggests that different analytical methods could be used to deliver similarly capable diagnostic capabilities. Further, the strength of the relationship between the best brain network metrics we use here and the CRS-R based diagnosis is comparable to that reported in previous literature that has employed EEG-based analysis (King et al, 2013;Sitt et al, 2014). PET (Stender et al, 2016) and TMS-EEG (Casarotto et al, 2016) have been shown to perform better, but both require much more complex technology that is either impossible or difficult to deploy at the patient's bedside.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We then analyzed in detail the univariate markers that are usually more contributive to the multivariate classifier by comparing the topographies from the previously recorded and diagnosed patients with this patient. Detailed analysis further revealed that patterns of spectral power of EEG (in delta and alpha band), complexity markers (spectral entropy, permutation entropy and Komolgorov-Chaitin complexity), and functional connectivity (weighted Symbolic Mutual Information, wSMI [12] ) were strongly supportive of a conscious state, rather than of a VS/UWS or even MCS ( Figure 2). As expected, univariate markers of auditory event-related potentials were not contributive given patient's deafness.…”
Section: Beyond Behaviormentioning
confidence: 99%